Comparison of Telfa Rolling and a Closed Washing System for Autologous Fat Processing Techniques in Postmastectomy Breast Reconstruction. Issue 3 (September 2020) - Valmadrid, Al C.; Kaoutzanis, Christodoulos; Wormer, Blair A.; Farinas, Angel F.; Wang, Li; Al Kassis, Salam; Perdikis, Galen; Braun, Stephane A.; Higdon, Kent K.
Abstract : Background: The purpose of this study was to compare the commonly used fat grafting techniques—Telfa rolling and a closed washing system—in breast reconstruction patients. Methods: Consecutive patients undergoing fat grafting were retrospectively reviewed and grouped by technique. Patients with less than 180 days of follow-up were excluded. Demographics, operative details, and complications were compared using univariate analysis with significance set at p < 0.05. Results: Between January of 2013 and September of 2017, 186 women underwent a total of 319 fat grafting procedures. There was no difference in demographics, number of procedures performed, volume of fat grafted, and number of days after reconstruction that fat grafting was performed between groups ( p > 0.05). Telfa rolling patients had longer operative times for second fat grafting procedures (implant exchange often completed prior) [100.0 minutes (range, 60.0 to 150.0 minutes) versus 79.0 minutes (range, 64.0 to 94.0 minutes); p = 0.03]. Telfa rolling breasts had more palpable masses requiring imaging (26.0 percent versus 14.4 percent; p = 0.01) and an increased incidence of fat necrosis (20.6 percent versus 8.0 percent; p < 0.01). The closed washing system was found to be an independent predictor of decreased rates of imaging-confirmed fat necrosis (OR, 0.29; p = 0.048). There was no difference in fat necrosis excision or cancer recurrence between the groups. Conclusion: The closed washing system was independently associated with decreased rates of imaging-confirmed fat necrosis compared to Telfa rolling without an increase in other complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.